A transcriptomics model of estrogen action in the ovine fetal hypothalamus: evidence for estrogenic effects of ICI 182,780 - Rabaglino, Maria Belen (2018)
Estradiol plays a critical role in stimulating the fetal hypothalamus?pituitary?adrenal axis at the end of gestation. Estradiol action is mediated through nuclear and membrane receptors that can be modulated by ICI 182,780, a pure antiestrogen compound. The objective of this study was to evaluate the transcriptomic profile of estradiol and ICI 182,780, testing the hypothesis that ICI 182,780 antagonizes the action of estradiol in the fetal hypothalamus. Chronically catheterized ovine fetuses were infused for 48 h with: vehicle (Control, n = 6), 17β‐estradiol 500 μg/kg/day (Estradiol, n = 4), ICI 182,780 5 μg/kg/day (ICI 5 μg, n = 4) and ICI 182,780 5 mg/kg/day (ICI 5 mg, n = 5). Fetal hypothalami were collected afterward, and gene expression was measured through microarray. Statistical analysis of transcriptomic data was performed with Bioconductor‐R and Cytoscape software. Unexpectedly, 35% and 15.5% of the upregulated differentially expressed genes (DEG) by Estradiol significantly overlapped (P < 0.05) with upregulated DEG by ICI 5 mg and ICI 5 μg, respectively. For the downregulated DEG, these percentages were 29.9% and 15.5%, respectively. There was almost no overlap for DEG following opposite directions between Estradiol and ICI ICI 5 mg or ICI 5 μg. Furthermore, most of the genes in the estrogen signaling pathway after activation of the epidermal growth factor receptor followed the same direction in Estradiol, ICI 5 μg or ICI 5 mg compared to Control. In conclusion, estradiol and ICI 182,780 have estrogenic genomic effects in the developing brain, suggesting the possibility that the major action of estradiol on the fetal hypothalamus involves another receptor system rather than estrogen receptors.